Herramientas de transmisión comunitaria: libelos y pasquines en la Navarra moderna - RUIZ ASTIZ, Javier (Historia y Comunicación Social, 2010)
Libels and lampoons became during the Early Modern Age an elementary tool of community sociability. In the present article the objective is to deepen in its analysis like instruments of social confrontation next to its relevance like average creators of opinion states. Throughout this study I will try to contextualise in what conditions, how, when and why they took place this type of manifestations.